Pendampingan Perencanaan Drainase Sederhana sebagai Upaya Pengurangan Genangan Air di Lingkungan Permukiman - Hesty Septarina; Sinta Wati (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2026)
Inundation in residential areas is often caused by inadequate drainage capacity, sediment accumulation, solid waste blockage, limited infiltration area, and the absence of routine maintenance. This community service activity aimed to assist residents in identifying inundation points, understanding basic drainage principles, and preparing simple drainage planning recommendations that can be implemented gradually at the neighborhood scale. The method consisted of coordination with local partners, participatory field observation, technical education, simple drainage planning assistance, and evaluation through discussion and participant feedback. The activity produced an inundation-point map, a list of drainage problems, simple technical recommendations, and a community-based maintenance plan. The results showed that residents became more capable of recognizing the relationship between rainfall runoff, channel slope, channel capacity, sediment, waste, and outlet conditions. The assistance also encouraged residents to prioritize routine cleaning, minor channel normalization, infiltration facilities, and coordination with local government for segments requiring detailed technical surveys. This activity indicates that simple civil engineering assistance can strengthen community awareness and support practical efforts to reduce local inundation risk in residential areas.